Determinants of performance improvement of Micro, Small, and Medium Enterprises (MSME) in the border market of North Timor Central District – Timor Leste - Margareta Diana Pangastuti; Frederic Winston Nalle; Bernadus Gawa Rado; Adriana Kolo (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2023)
This study examines the impact of financial literacy, technological innovation, government support, and subjective norms on the performance of Micro, Small, and Medium Enterprises (MSMEs) in the North Central Timor District (TTU)-Timor Leste Border Market. Furthermore, it seeks to identify appropriate strategies for enhancing MSME performance in this region. Both multiple linear regression analysis and descriptive analysis were employed as research methods. The study population included all MSMEs in the TTU District, totaling 693 entities. The researchers employed a purposive sampling technique based on the Slovin formula, selecting 80 respondents as research samples. The findings indicated that technological innovation, government support, and subjective norms significantly affect MSME performance in the TTU-Timor Leste Border Market. To improve the performance of MSMEs, various strategies can be implemented. These encompass the enhancement of financial literacy through training and mentoring programs, adopting e-commerce within the digital economy, and improving human resource quality and product standards. Other strategies include fostering partnerships among institutions, cultivating an investment-friendly bureaucracy, implementing product labeling, establishing legal business associations, and promoting motivation and self-confidence.